2022
DOI: 10.3389/fpsyt.2022.884828
|View full text |Cite
|
Sign up to set email alerts
|

The mirror mechanism in schizophrenia: A systematic review and qualitative meta-analysis

Abstract: BackgroundMirror neuron system (MNS) consists of visuomotor neurons that are responsible for the mirror neuron activity (MNA), meaning that each time an individual observes another individual performing an action, these neurons encode that action, and are activated in the observer's cortical motor system. Previous studies report its malfunction in autism, opening doors to investigate the underlying pathophysiology of the disorder in a more elaborate way and coming up with new rehabilitation methods. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 132 publications
0
1
0
Order By: Relevance
“…Dysfunctional MNS activity has been associated with social cognitive impairments across neuropsychiatric disorders (reviewed in Chan and Han 2020; Jeon and Lee 2018). In Sz, studies have reported reduced MNS activation during action observation (Mehta et al 2014;Valizadeh et al 2022), in association with impaired TOM performance (Choe et al 2018) and negative symptom severity (Schilbach et al 2016). In recent studies (Martinez et al 2018;Martinez et al 2019;Martínez et al 2022), we have observed reduced MT+ activation in Sz in response to simple motion stimuli which correlate with reduced FER to static emotional faces (Martinez et al 2018), suggesting a potential involvement of MT+ deficits even to static-only stimuli.…”
Section: Introductionmentioning
confidence: 62%
“…Dysfunctional MNS activity has been associated with social cognitive impairments across neuropsychiatric disorders (reviewed in Chan and Han 2020; Jeon and Lee 2018). In Sz, studies have reported reduced MNS activation during action observation (Mehta et al 2014;Valizadeh et al 2022), in association with impaired TOM performance (Choe et al 2018) and negative symptom severity (Schilbach et al 2016). In recent studies (Martinez et al 2018;Martinez et al 2019;Martínez et al 2022), we have observed reduced MT+ activation in Sz in response to simple motion stimuli which correlate with reduced FER to static emotional faces (Martinez et al 2018), suggesting a potential involvement of MT+ deficits even to static-only stimuli.…”
Section: Introductionmentioning
confidence: 62%
“…These include the middle frontal gyrus (MFG), sensorimotor cortex (SMC), supplementary motor area (SMA), posterior superior temporal sulcus (pSTS) and the putamen ( Bonini, 2017 , Caspers et al, 2010 , Errante and Fogassi, 2020 , Ferrari et al, 2017 , Molenberghs et al, 2012 ). Disrupted MNS activity during action observation/imitation has been reported in several neuropsychiatric disorders (reviewed in Chan and Han, 2020 , Jeon and Lee, 2018 ) including Sz ( Brown et al, 2016 , Mehta et al, 2014b , Thakkar et al, 2014 , Valizadeh et al, 2022 ). In Sz, altered MNS activity has also been associated with impaired TOM performance ( Choe et al, 2018 ) and greater symptom severity ( Mehta et al, 2014a , Saito et al, 2018 , Schilbach et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%